Rheological properties of Josapine pineapple juice at different stages of maturity. - Shamsudin, Rosnah; Wan Daud, Wan Ramli; Takrif, Mohd Sobri; Hassan, Osman; Ilicali, Coskan (Blackwell Publishing, 2009)
The rheological behaviour of Josapine pineapple juice with at various maturity stages was studied at a wide range of temperature (5–65 °C) and concentration (4–14 °Brix) using a rotational rheometer as the measuring system. The results show that josapine pineapples juice demonstrated a Newtonian behavior and is influenced by maturity stage, temperature and concentration. The Arrhenius typed equation successfully describe the effect of temperature on the viscosity, on the other hand, the effect of concentration can be described better using exponential equation. Finally, an equation describing the combined effect of temperature and concentration on viscosity at different stages of maturity was successfully developed.